Ethnopedagogics as A Learning Strategy in Multicultural Education in Indonesian Language Subjects - Elisabet Mangera; Roni La'biran; Resnita Dewi (AL-ISHLAH: Jurnal Pendidikan, 2026)
Indonesia’s multicultural context presents both opportunities and challenges for education, particularly in integrating local cultural values into formal learning. Ethnopedagogy has emerged as a culturally responsive approach that connects curriculum content with students’ socio-cultural backgrounds. This study examines the implementation of ethnopedagogics as a learning strategy in Indonesian language subjects within a multicultural classroom setting in a rural area of Tana Toraja. This research employed a qualitative case study design conducted at UPT SMP Negeri 3 Bonggakaradeng, South Sulawesi. Data were collected over six weeks through participatory observation, in-depth interviews with three Indonesian language teachers, focus group discussions involving twelve students, and document analysis of lesson plans and teaching materials. The data were analyzed using thematic analysis with source and method triangulation to ensure validity. The findings indicate that the integration of local cultural elements, particularly Toraja folklore, increased students’ learning motivation, classroom engagement, and appreciation of cultural diversity. Ethnopedagogic-based learning fostered empathy, intercultural communication, and mutual respect among students from different ethnic backgrounds. Teachers also reported improved classroom dynamics and stronger teacher–student relationships. However, challenges included limited culturally representative resources and insufficient teacher training. The study demonstrates that ethnopedagogics can function as an effective multicultural learning strategy by promoting inclusive, culturally responsive education. Despite implementation challenges, this approach contributes to strengthening social cohesion and contextualizing language learning in culturally diverse settings.